Comparative Study of the Perspectives on the Impact of a Culturally Responsive Picture Exchange Communication System for Children With Autism Spectrum Disorder in the United Arab Emirates - Safi, Mohammed; Opoku, Maxwell Peprah; Alshamsi, Mariam; Abu-shariha, Ahmad Hassan (Frontiers in Pediatrics, 2022)
Background: Picture Exchange Communication System (PECS) is a widely accepted way to develop the communication skills of children with developmental disabilities such as autism spectrum disorder (ASD). However, the efficacy of PECS has largely been studied in Western societies and little research is available regarding its role in the development of children with ASD in a non-Western cultural context. The purpose of this study was to compare parent and practitioner perceptions of the use of PECS for children with ASD in the United Arab Emirates. Method: A new scale made up of three subscales was used to collect data from parents and practitioners who were either related to or working with a cohort of children with ASD. The data were analyzed using SPSS and subjected to computation of means, t-tests, analysis of variance, binary logistical regression, and two-way factorial analysis of variance. Results: The results showed uncertainty or neutrality among the parents and practitioners toward the use of PECS. Variables such as age, years of experience using PECS, and gender were noted to influence perceptions of PECS. Conclusion: The need for policymakers to consider developing regular training for parents and practitioners on the use of PECS and other implications are discussed.